2015
DOI: 10.1103/physrevb.92.224514
|View full text |Cite
|
Sign up to set email alerts
|

Electron pairing in the presence of incipient bands in iron-based superconductors

Abstract: Recent experiments on certain Fe-based superconductors have hinted at a role for paired electrons in "incipient" bands that are close to, but do not cross the Fermi level. Related theoretical works disagree on whether or not strong-coupling superconductivity is required to explain such effects, and whether a critical interaction strength exists. In this work, we consider various versions of the model problem of pairing of electrons in the presence of an incipient band, within a simple multiband weak-coupling B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
114
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(134 citation statements)
references
References 52 publications
16
114
4
Order By: Relevance
“…In stark contrast to previous proposals, our here predicted deep Fermi sea Cooper pairing does not depend upon interband scattering processes mediated by bosons at large wavevectors, like e.g. antiferromagnetic spin fluctuations [27,28] or the conventional short-ranged in real space EPI [29].In the presence of a strong inhomogeneous dielectric background, the EPI develops a pronounced forward scattering peak [18,30]. Here, the interface-induced EPI is modelled by a dispersionless mode at Ω=81 meV [21] coupled to FeSe electrons via the functional form g(q) = g 0 exp (−|q|/q c ) with q c = 0.3a −1 [6], with a the FeSe lattice constant.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…In stark contrast to previous proposals, our here predicted deep Fermi sea Cooper pairing does not depend upon interband scattering processes mediated by bosons at large wavevectors, like e.g. antiferromagnetic spin fluctuations [27,28] or the conventional short-ranged in real space EPI [29].In the presence of a strong inhomogeneous dielectric background, the EPI develops a pronounced forward scattering peak [18,30]. Here, the interface-induced EPI is modelled by a dispersionless mode at Ω=81 meV [21] coupled to FeSe electrons via the functional form g(q) = g 0 exp (−|q|/q c ) with q c = 0.3a −1 [6], with a the FeSe lattice constant.…”
contrasting
confidence: 99%
“…In stark contrast to previous proposals, our here predicted deep Fermi sea Cooper pairing does not depend upon interband scattering processes mediated by bosons at large wavevectors, like e.g. antiferromagnetic spin fluctuations [27,28] or the conventional short-ranged in real space EPI [29].…”
contrasting
confidence: 99%
“…5 The large electron doping and the resulting Fermi surface with only electron pockets directly challenge the Fermi-surface-nesting driven, purely electronic pairing mechanism. 18,19 One way to reconcile such a scenario is by taking account of the holelike band located below the Fermi level at the Γ point, 20,21 since the band top is less than 100 meV away from the Fermi level, i.e., an "incipient" band 21 that might fall in the low-energy cutoff of the bosons mediating pairing. The substrate, however, also influences the phononic degrees of freedom and the electron-phonon (e-ph) interaction, which can lead to phonon contributions to the supercon-ductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The boson was initially hypothesized to be an O phonon mode and subsequently observed on bare SrTiO 3 (001) [11]. Model calculations have demonstrated that phonons can enhance spin-fluctuation-mediated pairing in FeSe [5,12,13]. Others have argued that phonons alone can account for a significant portion of the high T c [14,15].…”
Section: Introductionmentioning
confidence: 99%